A COMPREHENSIVE STUDY OF THE STABILITY OF LATERAL ROCKS WITH A SUPPLE SUPPORT (World Science, 2020)
A complex of analytical studies of the stability of lateral rocks with a supple support, where the coal seam roof was a beam model, some laboratory experiments on samples made from optical and equivalent materials, as well as some mine experiments were was carried out. As a result of the studies, it was found that the stability of lateral rocks with a supple support of crushed rock depended on the compaction of the backfill array on which the roof rocks were based. It was experimentally proved that with external force, the coefficient of compaction of the backfill array changes according to the hyperbolic dependence, the maximum values of which were determined as a result of compaction of the supple support consisting of heterogeneous fractions of the starting material of a certain bulk density. The change in the stress-strain state of the lateral rocks in the coal array with a roadway depended on the bending stiffness of the stratified rock mass and the parameters of flexible structures used to support the roadway. When supporting the roadways with supple support structures, the convergence of the lateral rocks on the contour of the stoop roadway was observed exponentially until the support was completely compressed, while supporting the roadways with coal pillars, the displacement of the rocks on the contour of the roadway increased having linear dependence due to the destruction of the pillar. The stability of the lateral rocks, which determines the operational state of the excavation roadways, was ensured by the use of supple supports or stowing the mined-out space, taking into account the reasonable granulometric content of crushed rock, which ensured the maximum values of the compaction coefficient of the backfill array when the roof and coal seat got deformed.